(3WhGdY GdCfhGQ ef eWGdY GdCfXGQs - (3YHO Gddg Hf YeQ Hf eMeO Hf Ydj , GdTjQGRj GdHjVGhj, CHh SYjO CHh GdNjQ fGUQ GdOjf,J (B685 (3g` s
(3ChdgG (B:s
(3GdMeO def hLH hLhOg hHbGg hGeJfY YOeg hafGg hHYO aEf CYXe GdYdhe ehVhYkG eHfi bhGYO GdTQY hCSGSgG hQFjS eYGde GdOjf hEf cJGHfG gPG jTJed Ydi YbGFO GdeYbhd hfNH Gdefbhd s
(3BNQgG (B:s
(3hMci ef BKGQge faYfG Gddg HeMHJge CLeYjf Je cJGH WhGdY GdCfhGQ ef eWGdY GdCfXGQ JUfja GdTjN GdHjVGhi s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B110 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B298s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3CUhd Gdabgs